A nursing clinical data model for neuromuscular processes: content analysis of the Portuguese nursing customization - Neves, Hugo (2019)
This study targets the development of a nursing clinical data model for neuromuscular processes. To achieve this purpose, content analysis based on Bardin’s perspective was performed on the Portuguese nursing local customizations regarding neuromuscular processes, with the International Classification for Nursing Practice concepts and the ISO 18104:2014 used as encoding rules. From analysis of the data, a total of 1766 diagnoses were related to neuromuscular processes. After application of exclusion criteria, a corpus with a total of 900 diagnoses was subjected to content analysis. After application of the encoding rules, a total of 81 context units were obtained, and through an inductive approach, were defined into three categories: clinical findings (e.g. aphasia); negative judgment diagnoses (e.g. impaired communication); transition properties (e.g. preparation and knowledge). These interpretations were validated by experts in the field. This study not only demonstrates the need to standardize data, but also the importance of neuromuscular processes in nursing practice. We hope this study will guide the definition of a nursing clinical data model that will help in increasing complexity in the level of care provided with high impact in the patient’s quality of life.